Detection of Latent HIV-1 Infection and Drug Resistant Mutation Testing in Nepal: HIV-1 env V3 DNA Sequence and RT Gene (M184V) Mutation - Shrestha, Rupendra; Khadka, Sundar; Wagle, Susbin Raj; Sapkota, Alisha (Nepal Journal of Biotechnology, 2016)
HIV-1 resistance to antiretroviral therapy (ART) is a crucial issue, despite various effective drugs are available for the treatment. Although the viral RNA is suppressed below the detection limit (<50 copies/ml) with the use of potent antiviral drugs, the mutation can be archived in the cellular reservoir as proviral DNA. The detection of proviral DNA and mutation screening in HIV 1 RNA for genotypic resistance is the sole basis for monitoring the effectiveness of ART. Our study aim to access the extent of latent HIV infections by detecting env V3 DNA and also testing of M184V (meth184val; ATG - GTG substitution at 184th codon) specific mutations in HIV-1 RT gene to monitor the effectiveness of ART. The HIV-1 env V3 DNA sequence was amplified using multiple upstream and downstream primes to show the latent HIV infections, whereas polymerase chain reaction- restriction fragment digestion assay (PCR-RFDA) was used for testing M184V mutation in HIV-1 RT gene. In the study, out of 15 HIV infected patient blood samples, 12 shows amplification of env V3 DNA, confirming the latent HIV infections while 3 were negative for env V3 DNA. HIV-1 RT gene tested for M184V mutation in all 15 samples showed wild type after analysis using PCR-RFDA. After digestion with CviAII, three bands were observed in wild type whereas in mutant only two bands. Although the study shows negative for the M184V resistance mutation, screening of various panels of drug resistance mutations should be performed in recently infected HIV-1 patients for planning the effective ART strategy. The data is not enough to compare the overall scenario of the Nepal thus warrant urgency for large scale study with standard genotypic tools.